What Do We Know and We Do Not Know About Cardiovascular Autonomic Neuropathy in Diabetes - Pop-Busui, Rodica (2012)
Cardiovascular autonomic neuropathy (CAN) in diabetes is generally overlooked in practice, although awareness of its serious consequences is emerging. Challenges in understanding the complex, dynamic changes in the modulation of the sympathetic/parasympathetic systems’ tone and their interactions with physiologic mechanisms regulating the control of heart rate, blood pressure, and other cardiovascular functions in the presence of acute hyper-or-hypoglycemic stress, other stressors or medication, and challenges with sensitive evaluations have contributed to lower CAN visibility compared with other diabetes complications. Yet, CAN is a significant cause of morbidity and mortality, due to a high-risk of cardiac arrhythmias, silent myocardial ischemia and sudden death. While striving for aggressive risk factor control in diabetes practice seemed intuitive, recent reports of major clinical trials undermine established thinking concerning glycemic control and cardiovascular risk. This review covers current understanding and gaps in that understanding of the clinical implications of CAN and prevention and treatment of CAN.